Obstructive sleep apnea syndrome and cognition in Down syndrome. (29th January 2014) - Breslin, Jennifer; Spanò, Goffredina; Bootzin, Richard; Anand, Payal; Nadel, Lynn; Edgin, Jamie
Abstract : Aim: Good‐quality sleep is essential for normal learning and memory. Sleep fragmentation and disrupted sleep architecture are commonly observed throughout the lifespan of individuals with Down syndrome, a condition marked by cognitive deficits emerging within the first few months of life. While obstructive sleep apnea syndrome (OSAS) is known to contribute to the loss of sleep quality in Down syndrome, its relation to cognitive and behavioral impairment remains poorly understood. Method: Using ambulatory polysomnography, we measured sleep in an unreferred community‐based sample of 38 individuals with Down syndrome (15 males, 23 females; mean age 9y 7mo (SD 1y 9mo), range 7–12y). Cognitive outcomes were assessed with the Arizona Cognitive Test Battery, a set of psychometric measures designed and validated for this population. Results: Among children with Down syndrome, mean Verbal IQ score ( p =0.006) was 9 points lower in those with comorbid OSAS (apnea–hypopnea index >1.5) than in those without OSAS, and performance on measures of cognitive flexibility was poorer ( p =0.03). In addition, those with OSAS showed increased light‐stage sleep ( p =0.009) at the expense of slow‐wave sleep ( p =0.04). Interpretation: These findings demonstrate a relation between OSAS and cognitive outcomes in Down syndrome. More work is required to fully understand the mechanisms underlying the links between poor sleep and impaired cognitive function. Overall, these findings highlight the importance of adequate sleep in typically and atypically developing populations. What this paper adds: Obstructive sleep apnea syndrome is associated with some cognitive deficits in children with Down syndrome. Verbal IQ was 9 points lower in children with OSAS and Down syndrome, who also showed executive function deficits. These differences were found in children of similar age, BMI, and health status. Children with a dual diagnosis of Down syndrome and OSAS showed less slow‐wave sleep and more light‐stage sleep.